LONG TERM EFFECT OF CAFFEINE INTAKE ON SERUM ESTROGEN LEVELS AMONG FEMALES OF CHILD BEARING AGE- A REVIEW - Malay, Kausalyah Krisna; Malay, Sheersha; Priyadarshoni S, Pavithra; Ganapathy, Dhanraj (International Journal of Psychosocial Rehabilitation, 2019)
Many studies have indicated that caffeine consumption among women of child-bearing age has its effect on estrogen levels. The variation in estrogen levels associates with disorders such as endometriosis, osteoporosis, endometrial, breast and ovarian cancers. Long term caffeine consumptions potentials to influence estrogen levels over a long period of time and thus it make sense to take caffeine consumption into account when designing studies to understand these disorders. Caffeine, and probably dimethylxanthines, is ergogenic for most of the women. The mechanisms involve in the mode of actions of these compounds are varies and complex and extend well beyond the traditional explanation of sparing of muscle glycogen to probably involve fundamental aspects of muscle contractility. This probability mostly affects the level of estrogen in women especially in women with child bearing age. Caffeine acts as the suppressor for the estrogen hormone. Purpose of this review is to reveal the actual responces of caffeine towards the estrogen hormones.